Dielectric surface roughness scattering induced crosstalk performance of coupled MCB interconnects. (August 2021) - Sharma, Manvi; Rai, Mayank Kumar; Khanna, Rajesh
Abstract: A CMOS inverter driven equivalent single conductor model of capacitively coupled mixed CNT bundle (MCB) interconnects are taken to analyze the crosstalk induced time domain and frequency domain behaviors at 14 nm technology node for a temperature range (300–500 K). Four possible structures of MCB (e.g.S1, S2, S3 & S4) are analyzed by considering the dielectric substrate materials induced scattering. The most typical and consistent dielectric materials like silicon dioxide (SiO2 ), boron nitride (BN) and silicon carbide (SiC) are taken into account for studying the behavior of MCB depending upon dielectric surface roughness (DSR) scattering. A complete crosstalk (dynamic & functional) effect in terms of positive peaks, time duration and area of rise glitch is studied. The results revealed that MCB structure 'S4' is having less delay and more 3-dB frequency bandwidth in comparison to other structures of MCB. Moreover, S4 placed on SiC substrate material is depicting best results among other substrate materials. The bode stability of 'S4' on smooth surface and rough surface material is analyzed to validate the performance of 'S4SiC' in terms of phase and gain margin. It is also observed that the 3-dB frequency bandwidth of 'S4SiC'reduces with increase in temperature. Consequently, the amplitude of surface roughness parameter ( δ sr) plays an important role to analyze the performance of coupled interconnects of MCB in deep sub-micron (DSM) regime.